Protection of Biometric Information in the Framework of Aviation Security Procedures - Loboda, D.I. (Herald of Azerbaijan Engineering Academy, 2022)
One of the modern systems capable of countering the threat of terrorism in the air transport is a biometric identification system. An important issue in improving the aviation security system is also a protection of the biometric information and the biometric systems. The methodological basis of study, conducted in this article, is the analysis of mathematical models of the biometric identification systems. The application of software and hardware systems for the protection of biometric information is considered, and the main methods for identifying parameters and patterns of biometric identification are analyzed.